2008
DOI: 10.1128/jcm.00611-08
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Differentiation of Methicillin-Susceptible Staphylococcus aureus from Methicillin-Resistant S. aureus and MIC Determinations by Isothermal Microcalorimetry

Abstract: In this study, the use of isothermal microcalorimetry (IMC) for differentiation between methicillinresistant Staphylococcus aureus (MRSA) and methicillin-susceptible S. aureus (MSSA) and MIC determination was evaluated. It was possible to differentiate between MRSA and MSSA within 4 h, whereas the standard method required 24 h. The MICs of cefoxitin were successfully determined for MRSA and MSSA by using IMC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 9 publications
1
26
0
Order By: Relevance
“…However, knowledge of growth-related heat flow patterns in individual species might allow splitting the contribution of several (up to 3) pathogens using deconvolution algorithm. Similarly, slightly different heat flow pattern has been observed for methicillin-resistant S. aureus and for methicillin-susceptible S. aureus [24]. Therefore, use of pattern recognition algorithm should be used with care, and knowledge of heat flow pattern should be based on a rather large number of strains belonging to a single species and including resistant and susceptible strains to catch the ''natural variation'' within the considered species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, knowledge of growth-related heat flow patterns in individual species might allow splitting the contribution of several (up to 3) pathogens using deconvolution algorithm. Similarly, slightly different heat flow pattern has been observed for methicillin-resistant S. aureus and for methicillin-susceptible S. aureus [24]. Therefore, use of pattern recognition algorithm should be used with care, and knowledge of heat flow pattern should be based on a rather large number of strains belonging to a single species and including resistant and susceptible strains to catch the ''natural variation'' within the considered species.…”
Section: Discussionmentioning
confidence: 99%
“…coli 0.75 ± 0.11 0.94 ± 0.13 11 0.75-1.67 Roos et al [24] E. faecalis 0.74 ± 0.10 0.95 ± 0.13 11 0.81 ± 0.05 Vebo et al [25] P. mirabilis 1.31 ± 0.04 0.53 ± 0.02 9 0.40-1.02 Sosa et al [26] S. aureus 0.56 ± 0.20 1.42 ± 0.51 9 1.41 ± 0. 21 Bonkat et al [7] AUM artificial urine medium World J Urol (2013) 31:553-557 555 growth rate was slightly higher (4-16 %), resulting in shorter generation time.…”
Section: Discussionmentioning
confidence: 99%
“…Microcalorimetry can also reveal temporal details (such as thermal effect) that are not observable by other techniques (Batovska et al, 2007;Leng et al, 2007;Kwon et al, 2008). It has already been demonstrated that calorimetric methods can be used for fundamental studies of organisms' growth (von Ah et al, 2008;Yan et al, 2009b). Accordingly, microcalorimetry is a good method for evaluating the antibacterial activities of R. coptidis.…”
Section: Original Articlementioning
confidence: 99%
“…IMC measures the heat flow of biological processes (endo-or exothermic reactions) over time and has already been applied in various disciplines, including studies on food deterioration, drug shelf life (34), microbial processes, and the effects of different antimicrobial agents (6,39 …”
mentioning
confidence: 99%